Perancangan Dokumen Hazard Identification, Risk Assessment and Risk Control untuk Mengurangi Potensi Resiko Bahaya pada PT X - Krisnadinata, Ivan; Sutapa, I Nyoman (Jurnal Titra, 2019)
PT X is a factory that produce roasted peanuts and have in total 110 workers in the production process. Based on the historical data, there are 20-30 work accident that happened every year. Thus, this research aim to fix the OHS system management using Hazard Identification, Risk Assesment, and Risk Control (HIRARC) of OHSAS 18001 : 2007 clause. Based on the results of the Risk Assessment, there are 7 of high risk potentials, 21 of medium risk potentials, and 26 of low risk potentials. Continued by adopting Risk Control which aims to minimize the potential hazards of high and medium risks. The result of risk controls are carried out using 5 methods, which are elimination, substitution, engineering control, administrative control, and PPE, but the most commonly used method are the elimination, administrative control, and PPE.